Hubungan Tingkat Pengetahuan Dengan Upaya Pengendalian Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Karangmulya Kecamatan Karangpawitan Kabupaten Garut: Hubungan Tingkat Pengetahuan Dengan Upaya Pengendalian Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Karangmulya Kecamatan Karangpawitan Kabupaten Garut - Neng Sunarti; Iin Patimah (Institute Of Computer Science (IOCS), 2019)
Hypertension is one of common health problems. People with hypertension must be able to control their blood pressure to avoid serious diseases such as stroke, heart failure, kidney failure and other chronic diseases. To avoid seious desease good knowledge is needed. Controlling Blood pressure is the key to success for all people with hypertension to prevent severe increase in blood pressure.This research uses descriptive correlation method. Population is all people hypertension in the working area of district ??Karangmulya. 57 Sample taken by the Non Probability Sampling technique.The results showed that 40 respondent had a good level of knowledge (70.2%) and 33 respondent had prevent blood pressure 57.9%. From the results of statistical tests obtained p value 0.00 (<0.05), with correlation coefficient (r) of 0.609 that’s means there is a significant relationship between the level of knowledge about hypertension and prevention of blood pressure. this findings expected that in the future various parties can examine other factors related to the level of knowledge about hypertension and efforts to prevent recurrence in patients with hypertension, excluding the factors discussed in this study.